That's the One!: An Analysis of Eyewitness Identifications in Missouri and Their Impact on Cross-Racial Identification - Deionna Ferguson (Washington University Journal of Law & Policy, 2020)
As evidenced by the inconsistent eyewitness accounts of the shooting of Michael Brown, Jr., eyewitness identifications are generally unreliable. In addition, cross-racial misidentification, when the eyewitness is of a different race than the suspect, highlights the need to ensure the reliability of eyewitness identifications. This Note argues that Missouri should follow other Midwestern states in the adoption of procedures involving eyewitnesses. At a minimum, such procedures should include: double-blind procedures, instructions that the suspect may not be present in a lineup, ensuring that all non-suspect fillers are similar in appearance to the suspect, procedures for retrieving confidence statements, and procedures for voice or audio recordings of the identification procedures.
Keywords: eyewitness; eyewitness account; eyewitness identification; cross-racial; cross-racial identification; cross-racial misidentification; misidentification